A resilient life : you can move ahead no matter what - MacDonald, Gordon, 1939- (Nashville : Nelson Books, 2004)
Whose heart doesn't leap at the sight of a beautifully conditioned runner, effortlessly gliding along, stride-by-stride, mile-by-mile? And what runner gets to this place without a thankless-and often lonely-regimen of strategy and self-denial? Isn't this the perfect metaphor of what your heart is longing for-running life's race with intentionality and grace? With strength and focus?
Resilient people are committed to finishing strong: Quitting is not an option -- "Walking" is unthinkable -- Building resilience is a daily pursuit -- The face of aimlessness -- The face of a champion -- Resilient people run inspired by a big-picture view of life -- Resilient people have a sense of life-direction -- Resilient people foresee the great questions of life's passage -- Resilient people prepare to answer the great questions of life's passage -- Resilient people cultivate christian character -- Resilient people listen for a call from God -- Resilient people are confident in their giftedness -- Resilient people intend to live generous lives -- Resilient people run free of the weight of the past -- Repairing the past -- Resilient people respect the power of memory -- The power of memory -- Resilient people practice repentance -- Resilient people are quick to forgive -- Resilient people overflow with gratitude -- Resilient people squeeze the past for all its wisdom -- Resilient people train to go the distance -- Resilient people prepare themselves for the "emergencies" of life -- Resilient people know exactly what has to be accomplished -- Resilient people keep themselves physically fit -- Resilient people grow their minds -- Resilient people harness their emotions -- Resilient people trim their egos -- Resilient people open their hearts to the presence of God -- Resilient people run in the company of a "happy few" -- The value of lingering -- The peril of the solitary life -- How friendship works -- There are certain people.
Includes bibliographical references (pages 241-243).
Keywords: Resilience (Personality trait) -- Religious aspects -- Christianity; Resilience (Personality trait) -- Religious aspects -- Christianity